15 Coronary perforation during PCI between 2006 and 2013: an analysis of 527, 121 cases from the BCIS database. (24th April 2016) - Kinnaird, Tim; Kwok, Chun Shing; Kontopantelis, Evangelos; Ludman, Peter; Belder, Mark de; Anderson, Richard; Mamas, Mamas
Abstract : Introduction: As coronary perforation (CP) is a rare but serious complication of PCI the current evidence base is limited to small series. Using a national PCI database the incidence, predictors and outcomes of CP during PCI were defined. Methods: Data were collected from the BCIS dataset on all PCI procedures performed in England and Wales between 2006 and 2013. Multivariate logistic regressions and propensity scores were used to identify predictors of CP and its association with outcomes. Results: 1, 762 coronary perforations were recorded from 527, 121 PCI procedures (incidence of 0.33%). Patients with CP were more often female or older, with a greater burden of co-morbidity and underwent more complex PCI procedures. Factors independently predictive of CP included age (OR 1.03, 1.02–1.03, p < 0.001), previous CABG (OR 1.56, 1.27–1.91), left main (OR 1.52, 1.19–1.94) use of rotational atherectomy (OR 2.27, 1.74–2.96) and CTO intervention (OR 5.36, 4.48–6.42). Adjusted odds of adverse outcomes were higher for all major adverse coronary events including stroke, bleeding and mortality. Emergency surgery was required in 3% of cases. Predictors of mortality in patients with CP included age, diabetes, previous myocardial infarction, renal disease, ventilatory support, use of circulatory support and glycoprotein inhibitor use. Conclusions: Using a national PCI database for the first time the incidence, predictors and outcomes of coronary perforation were conclusively defined. Although CP occurred of PCI rarely it was strongly associated with poor outcomes.